Edge virtualization in multihomed vehicular networks - Silva, Miguel (2021)
Vehicular Networks (VANETs) are a critical component of a Smart City environment. They extended the connectivity plane with support for a wide range of applications, from safety to entertainment. Such services, when deployed outside the vehicular network, may imply an additional delay, which can be critical. In addition, these services become inaccessible whenever the vehicles lose contact with the infrastructure.This paper proposes a practical solution that aims to minimize the impact of the services' location and its inaccessibility in a VANET. The solution focuses on using Network Function Virtualization technologies to support the deployment of the services at the edge of a mobility-enabled multihomed VANET, thus allowing the services to be accessible in intermittent connectivity situations, as well as enabling lower delays for critical services. The results obtained show that the solution is capable of deploying services at the edge of the VANET with low delay and with a fast recovery when in handover and mobility scenarios.